Copolymerzation of L,L-lactide with epsilon-caprolactone by using novel zinc L-proline organometallic catalyst - Pandey, Asutosh K. (E-Polymers, 2010)
Copolyesters based on L, L-lactide (LA) and e-caprolactone (CL) with different LA: epsilon-CL ratios were synthesized by ring opening polymerization using zinc (L-proline) as a catalyst. Ring opening polymerization results in random P(L, L-lactide-epsilon-caprolactone) copolymers of molecular weights between 9,800 to 30,000 and block copolymer up to 51,800 Da. H-1 NMR spectroscopy analysis was used for calculation of monomer incorporation in the copolymer. FT-IR spectra were used to differentiate between random and block copolymer using carbonyl region splitting. C-13 quantitative NMR spectroscopy analysis coupled with information from TGA and DSC allowed determination of the polymer structure. Copolymers (CP-1, CP-2 and CP-3) prepared by ROP are random copolymer (h > 1), while CP-4 prepared by ROP (sequential addition of epsilon-caprolactone and L, L-lactide) has a multi block character (h < 1). The LA number-average sequence length (L-LA) decreased from 14 to 5 for LA-CL 80:20 to 50:50 copolymers prepared by ROP. The copolymer (CP-4) prepared by sequential addition showed the number-average sequence length (L-LA) to be 83.0.

Enhancement of thermal stability and phase relaxation behavior of chitosan dissolved in aqueous l-lactic acid: using `silver nanoparticles' as nano filler - Rana, V. K.; Pandey, Asutosh K.; Singh, Raj Pal; Kumar, B.; Mishra, Satyendra; Ha, Chang-Sik (Macromolecular Research, 2010)
Chitosan films with various compositions of silver nanoparticles were prepared by solution casting with an aqueous solution of chitosan and l-lactic acid. The chitosan/Ag nanocomposites were characterized by wide angle Xray diffraction (WAXD) and UV-vis spectroscopy. An analysis of the surface topography and size of the Ag nanoparticles (<= 100 nm) were characterized by scanning electron microscopy (SEM) and atomic force microscopy (AFM), respectively. Thermogravimetric analysis (TGA/DTA) confirmed the increase in thermal stability with increasing Ag nanoparticle content in the nanocomposites. Dynamic thermal analysis (DMA) was used to examine the phase relaxation behavior of chitosan and its nanocomposites. The conductivity of chitosan/Ag nanocomposites was considered with respect to the frequency. Contact angle measurements were used to characterize the surface twistability, surface cleanliness, and hydrophilic/hydrophobic nature of the surface.
Keywords: Chitosan; conductivity; contact angle; relaxation; silver nanoparticles

Synthesis and characterization of novel value added biodegradable poly(aleuritic acid) from renewable resources(shellac) and invertible amphiphilic behaviors in various solvents - Pandey, Asutosh K.; Nande, Smita S.; Selukar, Balaji S.; Garnaik, Baijayantimala (E-Polymer, 2010)
A novel biodegradable polymer poly(aleuritic acid) (PAA) ( M̄w 120,000) was prepared from aleuritic acid, which was obtained from renewable resources (Lac) by using tin catalyst. Aleuritic acid (AL) was protected at 9, 10 position by dimethoxy propane. The protected AL (Pro.AL) was further polymerized to obtain linear protected polyaleuritic acid (PAL) by dehydropolycondensation. Effects of various kinetic and thermodynamic parameters were studied. After polymerization, the deprotection of PAL was carried out. The synthesized PAL and PAA were characterized by using various techniques such as FT-IR, LC-MS, SEC, NMR (1H and 13C), 13C CP/MAS (Cross Polarization / Magic Angle Spinning) of solid PAA, DSC, SEM and TEM etc. The micelle and inverted micelle -structure in polar and nonpolar solvents are highlighted

Copolymerization of aleuritic acid with l-lactic acid and study the aggregation behavior in different solvents - Pandey, Asutosh K.; Garnaik, Baijayantimala (International Journal of Research in Pharmacy and Chemistry, 2013)
In this present work, we highlight the copolymerization of L-lactic acid (L-LA with protected aleuritic acid in presence of Lewis acid catalyst using dehyropolycondensation method. The resulted copolymers are pliable, soft, waxy or even viscous liquid copolymers influenced by the aleuritic acid content. The purpose of this study is to investigate the physical properties. In addition, deprotected copolymers focus micelle-like aggregates in various organic solvents and mixed organic solvent at various proportions.

Study of grafting of polylactic acid and its copolymer with 12-hydroxy stearic acid on the surface of MWCNT by 13CCP/MAS and AFM - Pandey, Asutosh K.; Garnaik, Baijayantimala (International Journal of Research in Pharmacy and Chemistry, 2013)
The purpose of this study to study the structure property relationship of grafted material on MWCNT, the determination of NMR nuclei spin-lattice (T1) and spin-spin (T2) relaxation times suggest that the broaden signals are associated with diamagnetic species namely the nanotube attached polymer moieties. the AFM image of PLA oligomer grafted MWCNTs and topography patterns comprised of height from 0-250 nm and the side lengths ranging from 0.0 to 7.7 µm. Surface patches are formed randomly distributed employing that the presence of side chain hanged at 12-postion in the copolymer grafted on MWCNTs.